THE METHAMORPHOSIS OF A COASTAL CITY (Case study SEMARANG METROPOLITAN) - Bambang Setyoko (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Many empirical researches on urban growth have been carried out in megapolitan cities like Jakarta, and Surabaya. Most theoretical studies in this particular problem have been concerned about the expanding urban areas. This study differs firstly, concerning urban growth in a coastal city named Semarang, and secondly using superimposed and descriptive analysis based on old city-map and field survey data. Base on mapping analysis and field survey, Semarang urban fringe areas indicated dualistic characteristics, a mixing of formal and informal, planned and un-planned settlements. Most of them are incrementally spreading, mixed and growth simultaneously. Semarang as a port and ex- Dutch colonial city just has been on the earlier stages of spatial and structural evolution. This stage has been characterized as “spill over and specialization” occurred in fringe areas and it would lead to poly-centric metropolis. New urban infrastructure network has a contribution to the mono-centric fragmenting and metamorphosing into a poly-centric metropolis. The main activities at urban core have been move sporadically and incrementally to fringe area. Middle class migrated out of the city centre into sprawl settlements on the fringe areas. The role of central city decline while fringe areas increase. These conditions raise complicated social problems.